Measurement of the B0s→μ+ μ- decay properties and search for the B0→μ+ μ- and B0s μ+ μ- γ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review, 2022)
An improved measurement of the decay B0s→μ+μ− and searches for the decays B0→μ+μ− and B0s→μ+μ−γ are performed at the LHCb experiment using data collected in proton-proton collisions at √s=7, 8 and 13 TeV, corresponding to integrated luminosities of 1, 2 and 6 fb−1, respectively. The B0s→μ+μ− branching fraction and effective lifetime are measured to be B(B0s→μ+μ−)=(3.09+0.46+0.15−0.43−0.11)×10−9 and τ(B0s→μ+μ−)=(2.07±0.29±0.03) ps, respectively, where the uncertainties include both statistical and systematic contributions. No significant signal for B0→μ+μ− and B0s→μ+μ−γ decays is found and the upper limits B(B0→μ+μ−)<2.6×10−10 and B(B0s→μ+μ−γ)<2.0×10−9 at 95% confidence level are determined, where the latter is limited to the range mμμ>4.9 GeV/c2. Additionally, the ratio between the B0→μ+μ− and B0s→μ+μ− branching fractions is measured to be Rμ+μ−<0.095 at 95% confidence level. The results are in agreement with the Standard Model predictions.